Music: from common "non language" to "uncommon" language - Franco Pistono; Valerio Ciarocchi (Pensa MultiMedia, 2022)
"Starting from the known of the other": this is an indication that those who work in the world of communication (and education) know. Music is not a language, but it has some properties, one of all, and the most evident, is that practically almost all of the human species makes "use" of it. However, due to the ability not to say, but to suggest, move, excite, it can be said to have "uncommon" qualities, superior to language itself. Like the language, each place in the world hosts different music, not only in the sense of "not equal", but structurally different, as an "alphabet". Today's world - in schools, this aspect can be grasped - is a world where students of all ethnicities, creeds and cultures converge. How to start from the known of the other, to really communicate, that is, to understand each other, building a common ground of encounter not "by subtraction", but by adding contents, to grasp and exploit - making it intelligible - the contemporary complexity? Music can be a way.